Report of the 16th Annual International Scientific Conference of the Montenegrin Sports Academy - Ivana Bavcevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The article is providing highlights of the 16th Annual International Scientifi c Conference 'Sport, Physical Activity and Health: Contemporary Perspectives', hosted by the Montenegrin Sports Academy. The event was held on April 4-7, 2019 in Dubrovnik, Croatia. The conference provided space for presentation research papers and related discussion, as well as for poster sessions. Besides welcoming invited speakers it also hosted CEEPUS Training School for students. The participants of the conference were welcomed by Professor Doctor Stevo Popovic, dean of the Faculty for Sport and Physical Education, University of Montenegro, as well as by Dusko Simonovic, president of the Montenegrin Olympic Committee. The conference was offi cially opened in the large conference hall of the Hotel Croatia in Cavtat by rector of the University of Montenegro, Danilo Nikolic. This prestigious event gathered 364 authors and 223 participants, coming from almost 50 countries.